BIAYA TRANSAKSI DAN PEMILIHAN SALURAN PEMASARAN KOPI ARABIKA GAYO: STUDI EMPIRIS DI PROVINSI ACEH - Noratun Juliaviani; Sahara Sahara; Ratna Winandi Asmarantaka (JSEP (Journal of Social and Agricultural Economics), 2022)
This study aims to analyze the effect of transaction costs on the selection of marketing channels by Gayo Arabica coffee farmers in the Central Aceh and Bener Meriah districts. This study uses a transaction cost economics approach (TCE) to explain the choice between cooperatives collectors and exporters' traders. Identification of transaction cost variables that affect marketing channel selection by farmers in Aceh Tengah and Bener Meriah districts using the probit model with E-Views 7.0 software. The results show that the transaction costs that affect the farmers’ decision in choosing marketing channels to collectors from cooperatives in Central Aceh Regency are the amount of time to seek price information and dummy access to prices and prices received by farmers. Meanwhile, in Bener Meriah Regency, transaction costs that affect farmers' decisions in choosing marketing channels to collectors from cooperatives are the price received by farmers, dummy access to credit to traders, and the length of payment from traders. This research has policy implications for improving Gayo Arabica coffee farmers' structure, behavior, performance, and welfare